Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Solve: 6sin square x - sinxcosx - cos square x =3

Solve:


6sin square x - sinxcosx - cos square x =3

Grade:12

2 Answers

Chetan Mandayam Nayakar
312 Points
10 years ago

use cos^2(x) =(1+cos2x)/2 sin^2(x) =(1-cos2x)/2 and sinxcosx = sin(2x)/2, solve the resulting equation for 2x and then divide by 2 to get x

vijesh jayan
49 Points
10 years ago

6sin2x-sinx.cosx-cos2x = 3

multiplying 2 on both sides we get

12sin2x-2sinx.cosx-2cos2x = 6

but we know that cos2x=1-sin2x  and  2sinx.cosx=sin2x

12sin2x-sin2x-2(1-sin2x) = 6

12sin2x-sin2x-2+2sin2x = 6

14sin2x-sin2x = 6+2 = 8

further simplify

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free